Placement of Branch Sales of "Dhian Milk Pie" on Bali Island by Using the Dominating Set Application - Muhlisatul Mahmudah (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2018)
One of the theories developed in graph theory is the dominating set. Dominating set is a concept of determining the minimum point on the graph with the provision of a point as dominating set to reach the point that is around it. The smallest cardinality of the dominating set is called the domination number denoted by (G). Given graph G with point V and E side, let D be a subset of V. If each point of VD is adjacent at least one point from D, then D is said dominating set in graph G. Currently a lot of applications from dominating set, one of which is placement of product sales branches. The product used is " pie susu dhian", pie susu is one of the typical Balinese foods that many Bai people and tourists enjoy, so it requires sales outlets in many shops and spread evenly so that tourists can find this pie susu in various parts of Bali , however, it is necessary to minimize the production and placement of pie susu branches so that they can be sold well. In the research focused application Placement of Sales Branches Of “Pie Susu Dhian” In Bali In Dominating Sets Application Keywords: dominating set, pie susu dhian